Examining links between social withdrawal subtypes and internalizing problems among Italian primary school children. Issue 2 (4th March 2023) - Sette, Stefania; Zava, Federica; Baumgartner, Emma; Laghi, Fiorenzo; Coplan, Robert J.
ABSTRACT: The study aimed to explore links between social withdrawal subtypes and internalizing problems among children during the COVID-19 pandemic. Participants were N = 748 children (387 girls) aged 7–11 years ( M = 8.91, SD  = 1.07) attending primary schools in Italy. Children completed an online questionnaire assessing subtypes of social withdrawal (i.e., shyness, social avoidance, unsociability) and indices of internalizing problems (i.e., social anxiety, loneliness, depression). Among the results, shyness was positively associated with social anxiety, depression, and loneliness. Unsociability was related to depression but not to social anxiety and loneliness. Social avoidance was positively related to loneliness and depression (particularly among older children) and negatively associated with social anxiety (particularly among boys). Results are also discussed in terms of the implications of the different subtypes of social withdrawal in late childhood and early adolescence.